2018
DOI: 10.4236/health.2018.1011116
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Specifics of Self-Management towards Dealing with Cancer Pain among Adult Outpatients

Abstract: Purpose: This study aimed to identify specifics of self-management towards dealing with cancer pains among adult outpatients. Methods: Semi-structured interviews were conducted with 16 adult outpatients (9 males and 7 females) who suffered from cancer pain and the data obtained were analyzed using the qualitative synthesis method of KJ Ho. Results: An analysis of the results revealed these key findings for the following symbolic wording of the semi-structured interviews: Cooperative relationship with medical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The reasons for the positive evaluation of the program may be because the components of the program, patient goals, and details of the interventions were extracted based on the conceptual analysis of self-management toward dealing with cancer pain;[ 5 ] and including the results of an empirical qualitative study of adult outpatients with cancer pain;[ 2 ] and because the methods of the interventions of the CPSM program were determined based on the results of a literature review of educational interventions. A further reason for the high score in the appropriateness and clinical applicability of the program would be that the program was modified by obtaining opinions based on the practical experience of pharmacists and oncology nurses.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The reasons for the positive evaluation of the program may be because the components of the program, patient goals, and details of the interventions were extracted based on the conceptual analysis of self-management toward dealing with cancer pain;[ 5 ] and including the results of an empirical qualitative study of adult outpatients with cancer pain;[ 2 ] and because the methods of the interventions of the CPSM program were determined based on the results of a literature review of educational interventions. A further reason for the high score in the appropriateness and clinical applicability of the program would be that the program was modified by obtaining opinions based on the practical experience of pharmacists and oncology nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that outpatients reduce the doses of opioid analgesics due to worries about their tolerance and poisoning, and some patients suffer from drowsiness and constipation. [ 2 ] Considering these situations of outpatients in Japan, the use of the CPSM program would be clinically significant as it makes it easier for nurses to identify patients for intervention and to provide interventions that promote self-management of outpatients with cancer pain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations